Model for Developing the Agribusiness of Local Shallot Commodity, Topo Variety, in Tidore Islands City, North Maluku Province, Indonesia - Muhammad, Munawir; Rope, Ranita; Rajab, Albary (Agrikan Jurnal Agribisnis Perikanan, 2024)
The purpose of this research is to analyze the influence of factors such as the potential of local shallots, innovation, quality, processing, marketing, and institutional aspects on farmer participation and community empowerment. Agribussines development of the local shallot topo variety in Tidore Islands City, North Maluku Province. Additionally, the study aims to formulate an effective agribusiness development model for local shallots in Tidore Islands City, North Maluku Province. The sample used in this study consists of 100 individuals involved in the cultivation of local shallots. The analytical method employed in this research is Structural Equation Modeling (SEM), with data processing techniques utilizing Partial Least Squares (PLS)-based SEM. The results of the study indicate that several factors have a significant positive impact on community empowerment, the development of local shallots, and the food self-sufficiency of local shallots in North Maluku Province. These factors include the potential of local shallots, innovation, the quality of local topo shallots, and marketing, all of which contribute positively to community empowerment. Furthermore, community empowerment significantly impacts the development of local shallots, and in turn, the development of local shallots has a significant positive effect on the food self-sufficiency of local shallots.